ANALISIS PENGEMBANGAN USAHA KECIL HOME INDUSTRI SANGKAR AYAM DALAM RANGKA PENGENTASAN KEMISKINAN - Zuhri, Saifuddin (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
: Tujuan dari penelitian ini adalah untuk mengidentifikasi pengaruh-pengaruh langsung dan tidak langsung dari leverage, size, voluntary disclousure dan earning response coeffisient (ERC)The purpose of this study was to analyse small bussines (home industry) cock cage to clean poverty at the village of Kebomlati Tuban. Using SWOT (strenghts, weaknesses, Opportunities, and threats) analysis to get the solution of weaknesses small bussines cock cage, and used SWOT Matrict to formulate the strategy.To get efectivity and efficiency human resource by using modern tool in production - distribution â marketing. For unskill human resource give them special train about bussines management. Give the motivation to Bussines man to make them focuse on bussines development. Giving capital loan for Small Bussines by The Government is the good solutiom of modal. The implementation of SWOT Matric are to produce more and special for new market area, and make maximum production in dry season when the incresing of demand happened, make the good product will make it more interesting, maximalaised marketing, Â maintain costumer honesty by keeping characteristic and quality of product. Informasi laba merupakan hal yang paling direspon oleh investor karena memberikan gambaran mengenai kinerja perusahaan, namun informasi laba saja kadang tidak cukup untuk dijadikan sebagai dasar pengambilan keputusan investor karena ada kemungkinan informasi tersebut bias.Kata kunci : Earning Response Coefficient (ERC,) leverage, size, voluntary disclousureKeywords: Strategic, Small Bussines Development, Poverty